The National Health Plan 2030: Its Purpose and Directions of Development - Yumi Oh (Korean Society for Preventive Medicine, 2021)
The National Health Plan 2030 (HP2030) started to be prepared in 2017 and was completed and announced in December 2020. This study presents an overview of how it was established, the major changes in policies, its purpose, and future directions. This study analyzed the steps taken in the past 4 years to establish HP2030 and reviewed major issues at the international and governmental levels based on an evaluation of HP2020 and its content. HP2030 establishes 6 divisions and 28 topic areas, and it will continue to expand investments in health with a total budget of 2.5 trillion Korean won. It also established goals to enhance health equity for the first time, with the goal of calculating healthy life expectancy in a way that reflects the circumstances of Korea and reducing the gap in income and healthy life expectancy between regions. The establishment of HP2030 is significant in that it constitutes a sustainable long-term plan with sufficient preparation, contains policy measures that everyone participates in and makes together, and works towards improvements in universal health standards and health equity. With the announcement of HP2030, which includes goals and directions of the national health policy for the next 10 years, it will be necessary to further strengthen collaboration with relevant ministries, local governments, and agencies in various fields to concretize support for prevention-centered health management as a national task and to develop a health-friendly environment that considers health in all policy areas.